2022
DOI: 10.3390/buildings12020088
|View full text |Cite
|
Sign up to set email alerts
|

Causal Effects between Criteria That Establish the End of Service Life of Buildings and Components

Abstract: In the last decades, considerable work has been done regarding service life prediction of buildings and building components. Academics and members of the CIB W080 commission, as well as of ISO TC 59/SC14, have made several efforts in this area and created a general terminology for the concept of service life, which is extremely relevant for property management, life cycle assessment (LCA) and life cycle costs (LCC) analyses. Various definitions can be found in the literature that share common ideas. In fact, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 65 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Pushkar [5], based on Brand's concepts, showed that an LCA is highly dependent on the service life of each layer of a building. In addition, in a comprehensive review, Silva et al [6] noted that ignoring human behavior in a building can lead to erroneous predictions of the service life of buildings and their components.…”
Section: Introduction 1the Life-cycle Of Buildings and The Concept Of...mentioning
confidence: 99%
“…Pushkar [5], based on Brand's concepts, showed that an LCA is highly dependent on the service life of each layer of a building. In addition, in a comprehensive review, Silva et al [6] noted that ignoring human behavior in a building can lead to erroneous predictions of the service life of buildings and their components.…”
Section: Introduction 1the Life-cycle Of Buildings and The Concept Of...mentioning
confidence: 99%
“…Infrastructure deterioration: Many industrial buildings and facilities were built decades ago and are nearing the end of their useful life or have long since expired. This includes not only physical deterioration of materials, but also outdated HVAC systems, electrical networks, etc [7].…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance decisions at the end of building components' service lives are frequently driven by subjective motivations [1]. Subjective motivations can arise from various sources, including the building owner's personal preferences, sentimental attachments, aesthetic considerations, and individual/collective preferences or sense of taste [2]. It is important to acknowledge that subjective motivations for maintenance decisions, beyond technical requirements, hold value as they reflect the human element and emotional connections associated with buildings.…”
Section: Introductionmentioning
confidence: 99%